Brønsted Acid Catalyzed Tandem Defunctionalization of Biorenewable Ferulic acid and Derivates into Bio‐Catechol. (21st January 2020) - Bomon, Jeroen; Van Den Broeck, Elias; Bal, Mathias; Liao, Yuhe; Sergeyev, Sergey; Van Speybroeck, Veronique; Sels, Bert F.; Maes, Bert U. W.
Abstract: An efficient conversion of biorenewable ferulic acid into bio‐catechol has been developed. The transformation comprises two consecutive defunctionalizations of the substrate, that is, C−O (demethylation) and C−C (de‐2‐carboxyvinylation) bond cleavage, occurring in one step. The process only requires heating of ferulic acid with HCl (or H2 SO4 ) as catalyst in pressurized hot water (250 °C, 50 bar N2 ). The versatility is shown on a variety of other (biorenewable) substrates yielding up to 84 % di‐ (catechol, resorcinol, hydroquinone) and trihydroxybenzenes (pyrogallol, hydroxyquinol), in most cases just requiring simple extraction as work‐up. Abstract : Besonders (p)reiswert : Ferulasäure, eine biologisch erneuerbare Verbindung aus Reiskleie, wurde mithilfe von HCl und Wasser in Catechol, eine wichtige Grundchemikalie, überführt. Das Verfahren lässt sich auch auf eine Reihe anderer (biologisch erneuerbarer) Substrate anwenden.